Hubungan Antara Pes Planus Dengan Keseimbangan Dinamis Pada Murid MI Nurul Karim Colomadu - Agus Setyo Nugroho; Fadhila Firma Nurulita (Jurnal Keterapian Fisik, 2019)
Background: The ability to balance children at the age of development is very important to be reviewed, both in terms of balance sitting, standing, and walking. One of the factors that can cause balance disorders in children is musculoskeletal disorders in the form of deformity of the soles of the feet. The shape of the human foot is divided into three types, namely normal foot, pes planus and cavus foot according to the arcus structure or arches on the soles of the feet. Normally the arch is formed from the first 5 years with a 2-6 year age range. The critical period for arch formation is the age of 6 years (Campbell, 2012). In the early age of school there were 28% - 35% of children experiencing deformity of pes planus, 80% of which were categorized as "moderate". Methods: This research is a type of correlational research with a cross sectional design which aims to determine the relationship between pes planus and the dynamic balance in MI Nurul Karim Colomadu's students. The subjects used were grade 1-5 students with the condition of pes planus at MI Nurul Karim Colomadu, who had determined the inclusion and exclusion criteria. The number of subjects was 40 people with male and female sex from a total population of 92 people. Result: Using the Spearman Correlation Test Based on the table above, it is known that the value of p = 0.869 shows that there is no significant relationship between sex and dynamic balance. The value of r = 0.27 indicates the strength of the weak correlation. While the value of p = 0,000 shows there is a significant relationship between pes planus and dynamic balance. The value of r = -0,599 shows the strength of the medium correlation. Conclusion: One conclusion is 1. The prevalence of pes planus in girls is greater than that of boys, ie 16 boys and 24 girls have Pes Planus.